Gold Nanoparticles of Lactobacillus kimchicus DCY51T Suppressed Lipopolysaccharide-Stimulated Inflammatory Reactions in RAW264.7 Macrophage Cells - Sukweenadhi, Johan; Han, Yaxi; Jung, Dae-Hyo; Markus, Josua; Kim, Yeon-Ju; Kang, Se-Chan (Biosaintifika: Journal of Biology & Biology Education, 2024)
Excessive inflammation can lead to chronic diseases, necessitating the development of effective anti-inflammatory therapies. This study investigates the anti-inflammatory effects of gold nanoparticles (AuNps) synthesized using Lactobacillus kimchicus DCY51T, a probiotic strain from Korean kimchi. The objective is to explore the potential of DCY51T-AuNps in modulating inflammatory responses in RAW264.7 macrophage cells. Methods: AuNps were synthesized through a meticulous procedure involving the probiotic Lactobacillus kimchicus DCY51T. The isolation and subsequent cultivation of the RAW264.7 macrophage cell line in the DMEM medium formed the basis for the research methodology. Results: Following the establishment of the cellular platform, the cells were treated with DCY51T-AuNps, revealing a noteworthy reduction in the expression of key inflammatory mediators such as nitric oxide (NO), prostaglandin E2 (PGE2), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α). A pivotal aspect of the study focused on the inhibitory effects of DCY51T-AuNps on the lipopolysaccharide (LPS)-induced activation of the NF-κB/mitogen-activated protein kinase (MAPK) pathway within RAW264.7 cells. Conclusion: This inhibition was instrumental in modulating the inflammatory response, showcasing the potential therapeutic relevance of DCY51T-AuNps in combating inflammation. The novelty lies in using a probiotic-derived synthesis method, offering a sustainable and biocompatible approach to nanoparticle production. The benefit of this research not only underscores the anti-inflammatory prowess of DCY51T-AuNps on RAW264.7 macrophages but also contributes to the broader scientific discourse on the biomedical applications of gold nanoparticles synthesized from probiotic sources, potentially benefiting the development of new anti-inflammatory therapies and advancing nanomedicine.